2021
DOI: 10.1007/s40121-021-00485-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Forecasting Method for Estimating the Impact of Switching Pneumococcal Conjugate Programs: Evidence from Belgium

Abstract: Introduction: Since 2010, 10-valent (PCV10) and 13-valent pneumococcal conjugate vaccines (PCV13) have been available as part of infant national immunization programs. Belgium is as one of the few countries that implemented PCV13 (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), switched to PCV10 (2015)(2016)(2017)(2018) and then switched back to PCV13 (2018-present) after observing increases in disease. We assessed the impacts of both historical and prospective PCV choice in the context of the Belgian h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Switching from a higher-valent vaccine (PCV13) to a lower-valent vaccine (PCV10-GSK or PCV10-SII) in South Africa could result in a similar phenomenon. Our model may underestimate the true impact of switching from PCV13 to a PCV10 in South Africa, considering that a previous cost-effectiveness study from Belgium using the same model found that switching from PCV13 to PCV10-GSK led to more observed pneumococcal disease cases and deaths than the model estimated [ 15 ]. Therefore, it is important to retain a broad serotype coverage, as this remains relevant to epidemiological considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching from a higher-valent vaccine (PCV13) to a lower-valent vaccine (PCV10-GSK or PCV10-SII) in South Africa could result in a similar phenomenon. Our model may underestimate the true impact of switching from PCV13 to a PCV10 in South Africa, considering that a previous cost-effectiveness study from Belgium using the same model found that switching from PCV13 to PCV10-GSK led to more observed pneumococcal disease cases and deaths than the model estimated [ 15 ]. Therefore, it is important to retain a broad serotype coverage, as this remains relevant to epidemiological considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Serotype replacement trends were modeled to behave similarly to dynamics observed in Belgium and were set to re-emerge by a factor of 117–166% for serotypes not covered by PCV13. This may be a conservative assumption considering a previous cost-effectiveness study using the same model and assumption actually underestimated the epidemiologic impact of switching to a lower-valent vaccine in Belgium, where PCV13 was switched to PCV10-GSK in 2015 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains essential that investigational higher-valent vaccines continue to protect against serotypes contained in currently licensed vaccines and avoid removing vaccine pressure, given that uncovered serotypes can rebound and cause significant disease. Such resurgence was observed in Belgium following the switch from PCV13 to PCV10 in their NIP, which resulted in a significant increase of serotype 19A disease [ 65 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the analyses from this study are likely conservative and may underestimate the true impact of switching PCVs in light of serotype re-emergence data observed in Belgium. A Belgium case study that quantifies this underestimation was recently published, demonstrating that vaccine-type disease re-emergence may be more substantial than modeling exercises predict [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Belgium switched from PCV13-PFE to PCV10-GSK in 2015 because of potential vaccine-related cost-savings and a low perceived risk of disease re-emergence given the local epidemiology (i.e., suppressed vaccine-serotype disease) [ 12 ]. Thereafter, the incidence of IPD due to newly unprotected serotypes, primarily serotype 19A in the case of PCV10-GSK, increased exponentially and the Belgium Superior Health Council made a proactive recommendation to return to PCV13-PFE [ 13 ]. One might need to consider a similar possibility for serotypes 3, 4, and 18C in the case of a switch to PCV10-SII.…”
Section: Introductionmentioning
confidence: 99%